Effectiveness of Providing Psychoeducation to Dating Adolescents from Away in Bukittinggi - Syarif, Fathimah; Alhidaya, Julian Putri; Illahi, Amanda Permata; Rahmi, Annisa; Wahyuni, Siti Dinda (Universitas Islam Sultan Agung, 2025)
This research examines the effectiveness of providing psychoeducation on dating behavior among overseas teenagers in Bukittinggi City. Adolescents who migrate often face unique challenges and stressors, making them vulnerable to risky dating behavior. Psychoeducation aims to equip these youth with the knowledge and skills necessary to engage in healthy and respectful romantic relationships. This research used a quasi-experimental design with a one-group pretest-posttest design to evaluate the impact of psychoeducation. A total of 40 overseas teenagers, aged 15–19, participated in this research. They receive psychoeducation sessions specifically designed to address the issues they face related to dating in a new environment. The research results showed that there was a significant increase in teenagers' understanding and skills regarding healthy relationships after attending psychoeducation sessions. These findings suggest that psychoeducational interventions can be an effective strategy for helping overseas youth develop more positive dating behavior and reduce the risk of risky behavior in their relationships. This research makes an important contribution to the fields of health education and adolescent psychology and provides a basis for the development of more effective intervention programs to support the psychosocial well-being of overseas adolescents.